Hydrogeological-geotechnical Characterization and Analysis for Construction of a Subsurface Reservoir at a Coastal Site in the Nakdong Deltaic Plain, Busan, South Korea - Giao, Pham Huy; Park, Namsik (Earth and Planetary Science, 2023)
Store and recover clean groundwater from a man-made subsurface reservoir is useful for the development of coastal cities. A full-scale pilot field test of managed aquifer recharge (MAR) schemes were conducted in the Nakdong River plain, Korea. The process involved constructing a hydrogeological-geotechnical model based on investigation data, including the target aquifer that was located between 30 and 67 meters deep. The subsurface response to water pumping was analyzed, and this led to the creation of charts to determine the maximum allowable injection pressure and maximum recharge rate. For two factors of safety of 1.5 and 2.0, the maximum injection head rise was estimated to be 9.7 meters and 7.25 meters, respectively, corresponding to recharge rates of 5,000 and 3,800 m3/d. One-dimensional FE consolidation analyses were conducted for different groundwater drawdowns (2, 5, 10 and 15 m) and the results showed a good match with the monitored settlement and rebound for the 2-meter drawdown case. The study concluded that the injection rate could potentially be much higher than what was tested, which would increase the capacity of the subsurface reservoir. The lessons learned from this study are useful for similar coastal sites in terms of the application of MAR technology. ER